3D modelling of Ti-6Al-4V linear friction welds. - McAndrew, Anthony; Colegrove, Paul; Buhr, Clement (Cranfield University, 2016)
Experimental data set from the article "3D modelling of Ti-6Al-4V linear friction welds"Please see the introduction tab in the excel file for further details.
Keywords: 'Linear friction welding,'; 'finite element analysis.'; 'titanium'; 'Manufacturing Engineering not elsewhere classified'